Leaf morphology and anatomy of Rhizophora apiculata Blume. in Different Zonation of Sukadana Mangrove Tourism - Fitri, Anjelina; Zakiah, Zulfa; Rafdinal, Rafdinal (Jurnal Biologi Tropis, 2025)
Rhizophora apiculata is a mangrove species that lives in coastal areas. Differences in zoning will affect the growth of mangroves both morphologically and anatomically. This study aims to determine the morphological and anatomical characteristics of R. apiculata leaves in different zones. The research method used is descriptive method. Zone A is the zone near the sea water and zone B is the zone away from the water. Morphological observations were made directly, while anatomical observations were made through making preparations with the embedding method. Observations of leaf area parameters of R. apiculata in zone A showed a larger leaf area (83.11 ± 6.07cm2) compared to zone B (63.95 ± 8.61cm2). R. apiculata leaves in zone B had a higher number of stomata (24.42±5.60mm2) and stomatal density (124.43±28.43 cells/mm2) than zone A, which had a higher number of stomata (17.44±5.99mm2) and stomatal density (88.87±30.44 cells/mm2). Mesophyll tissue thickness parameters showed no significant difference between zone A and zone B. Parameters of salt glands showed significant differences between zone A and zone B. The results of the study, it can be concluded that differences in mangrove zones provide different responses and adaptations to the morphology and anatomy of R. apiculata leaves.